An exploration of the motivations and emotions of self-gifting in the Spa and wellness industry - Wilson, Max (2014)
The research aims to explore SGCB in the context of the spa and wellness industry, focusing on the nature, contexts and emotions associated with this form of SGCB. SGCB has been relatively well researched, although there is opportunity to discover more in the area. An exploratory approach was employed, interviewing 35 adults using the critical incident technique. A snowball sampling technique was used to ensure the participants had an interest in the topic. The study not only confirms existing SGCB literature, it also looks into the SGCB experience in the context of Spa and wellness. The situations were different from regular self-gifting, as participants were found to be in a negative mood entering into the SGCB experience. It highlighted the more therapeutic aspects of self-gifting and what consumers looked to gain from this behaviour.